Pengembangan Media Pembelajaran Video Animasi Berbasis Aplikasi Inshot Pada Tema 5 Kelas II SDN 040556 Juhar - Yemima Anastasya Br Ginting; Robenhart Tamba (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
This study aims to determine the feasibility, practicality and effectiveness of InShot application-based animated video learning media on theme 5 class II SDN 040556 Juhar. This type of research is a type of development research (Research and Development) using the 4D (Four D) development model. The instruments used are media expert validation sheets, material experts, educational practitioner assessments, student responses and tests (pre-test and post-test). The results of research related to feasibility show that the results of media expert validation fall into the "Very Feasible" category with a percentage of 93.33%. The results of material expert validation fall into the "Very Feasible" category with a percentage of 92%. The results of the assessment of educational practitioners and student responses related to practicality fall into the "Very Practical" category with a percentage of educational practitioner assessment of 96% and student responses of 93.66%. The results of research related to effectiveness showed that the post-test results reached 80 which was included in the "Very Effective" achievement level.